2019
DOI: 10.1113/jp278146
|View full text |Cite
|
Sign up to set email alerts
|

In vivokinetic study of materno‐fetal fatty acid transfer in obese and normal weight pregnant women

Abstract: Key points Placental structure and function can be modified as a result of maternal obesity affecting materno‐fetal fatty acids (FA) transport. We report for the first time, in humans and in vivo, the kinetics of placental FA transfer in normo‐weight and in normolipemic obese pregnant women using stable isotopes. The administration of different tracer FA with similar behaviour to the mother at different time points allows the collection of kinetic information on materno‐fetal transfer of FA despite only one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The procedure was highly similar to the gold-standard method for fatty acid enrichment analysis, where fatty acids are extracted, derivatized by addition of 3 M methanolic HCl, and incubated for 60 min at 90°C [12,13]. Except for the extraction and derivatizing reagent, these reaction conditions were kept the same.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure was highly similar to the gold-standard method for fatty acid enrichment analysis, where fatty acids are extracted, derivatized by addition of 3 M methanolic HCl, and incubated for 60 min at 90°C [12,13]. Except for the extraction and derivatizing reagent, these reaction conditions were kept the same.…”
Section: Resultsmentioning
confidence: 99%
“…With this method, the total plasma octanoate enrichment is analyzed. We altered our current methylation protocol [12,13] to facilitate isobutylation, which in comparison with methylation reduced the volatility of the derivatized octanoate, thereby reducing the risk of losses of the analyte during sample preparation. Direct derivatization in plasma limits the risk of contamination and, therefore, has improved accuracy and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…MBPK is the combination of classical pharmacokinetic modeling with elements describing the main mechanisms working in the system. MBPK founds on the mass conservation law and it has been used to inform several biological systems (Lofthouse et al, 2015;Perazzolo et al, 2015;Perazzolo et al, 2017;Perazzolo, 2017;Gázquez et al, 2019). Modeling procedure consisted of four steps: 1) Model structure building to represent the absorption mechanisms able to explain the long-acting pharmacokinetics exhibited by the nanoformulation; 2) Identifying the model parameters with mouse data; 3) Scaling the mouse model to get an NHP model; 4) Simulate a reference dose in the NHP model and observe results.…”
Section: Setting Up the Mechanism-based Pharmacokinetic Model For Nbimentioning
confidence: 99%
“…in this issue of The Journal of Physiology are the most thorough so far published (Gázquez et al . ). Their clever experimental design provided enough temporal concentration information to allow the estimation of fractional synthesis rate of free fatty acids and accumulation rates by the placenta in vivo .…”
mentioning
confidence: 97%
“…While Kolahi et al have estimated the uptake kinetics of free fatty acids in vitro (Kolahi et al 2018), little is known about the kinetics of fatty acid metabolism by the human placenta under physiological conditions. The kinetic studies reported by Gázquez et al in this issue of The Journal of Physiology are the most thorough so far published (Gázquez et al 2019). Their clever experimental design provided enough temporal concentration information to allow the estimation of fractional synthesis rate of free fatty acids and accumulation rates by the placenta in vivo.…”
mentioning
confidence: 99%